Gut microbiota and transcriptome analysis reveals a genetic component to dropping moisture in chickens - Tongyu Zhang; Tao Zhu; Junhui Wen; Yu Chen; Liang Wang; Xueze Lv; Weifang Yang; Yaxiong Jia; Changqing Qu; Haiying Li; Huie Wang; Lujiang Qu; et al. (Poultry Science, 2023)
ABSTRACT: High dropping moisture (DM) in poultry production has deleterious effects on the environment, feeding cost, and public health of people and animals. To explore the contributing genetic components, we classified DM of 67-wk-old Rhode Island Red (RIR) hens at 4 different levels and evaluated the underlying genetic heritability. We found the heritability of DM to be 0.219, indicating a moderately heritable trait. We then selected chickens with the highest and lowest DM levels. Using transcriptome, we only detected 12 differentially expressed genes (DEGs) between these 2 groups from the spleen, and 1,507 DEGs from intestinal tissues (jejunum and cecum). The low number of DEGs observed in the spleen suggests that differing moisture levels are not attributed to pathogenic infection. Fourteen of the intestinal high expressed genes are associated with water-salt metabolism (WSM). We also investigated the gut microbial composition by 16S rRNA gene amplicon sequencing. Six different microbial operational taxonomic units (OTUs) (Cetobacterium, Sterolibacterium, Elusimicrobium, Roseburia, Faecalicoccus, and Megamonas) between the 2 groups from jejunum and cecum are potentially biomarkers related to DM levels. Our results identify a genetic component to chicken DM, and can guide breeding strategies.